Word Learning by Preschool-Age Children: Differences in Encoding, Re-Encoding, and Consolidation Across Learners During Slow Mapping. - Gordon, Katherine R.; Lowry, Stephanie L.; Ohlmann, Nancy B.; Fitzpatrick, Denis (Journal of Speech, Language & Hearing Research, 2022)
Purpose: Children with typical development vary in how much experience they need to learn words. This could be due to differences in the amount of information encoded during periods of input, consolidated between periods of input, or both. Our primary purpose is to identify whether encoding, consolidation, or both, drive individual differences in the slow-mapping process. Method: Four- to 6-year-old children (N = 43) were trained on nine formreferent pairs across consecutive days. Children’s ability to name referents was assessed at the beginning and end of each session. Word learning was assessed 1 month after training to determine long-term retention. Results: Children with varying language knowledge and skills differed in their ability to encode words. Specifically, children varied in the number of words learned and the phonological precision of word forms at the end of the initial training session. Children demonstrated similarities in re-encoding in that they refined representations at a similar rate during subsequent sessions. Children did not differ in their ability to consolidate words between sessions, or in their ability to retain words over the 1-month delay. Conclusions: The amount of experience children need to learn words is primarily driven by the amount of information encoded during the initial experience. When provided with high-quality instruction, children demonstrate a similar ability to consolidate and retain words. Critically, word learning instruction in educational settings must include repeated explicit instruction with the same words to support learning in children with typical development and varying language skills.